PEDAGOGICAL MONITORING MECHANISMS FOR QUALITY IMPROVEMENT IN SCHOOL EDUCATION (Academia Science Repository, 2023)
In this article, forecasting the quality of education in general secondary schools is analyzed as a methodological problem. Also, the essence of the forecasting method is revealed. The study investigated the importance of educational monitoring for quality effectiveness.